Application of ATC/DDD Methodology to Evaluate of Antibiotic Use in a Trauma Centre General Hospital in Batam - Oktaviani, Fifin; Hamid, Hazrina Binti (PT FORMOSA CENDEKIA GLOBAL, 2024)
Wise use of antibiotics will prevent bacterial growth and reduce prolonged hospitalization. Actions to reduce the impact of antibiotic resistance can be carried out by evaluating antibiotics in terms of quantity and quality, quantitative evaluation using the (DDD) Defined Daily Dose method. The purpose of this study was to determine the general profile of antibiotic use quantitatively in hospitalized patients at a Riau Islands General Hospital in the trauma center ward. This study is observational non-experimental, data was taken retrospectively, from July to September 2023. Data analysis of this study used the quantitative method (ATC) Anatomical Therapeutic Chemical Classification / (DDD) Defined Daily Dose with a sample size of 138 patient medical records that met the inclusion criteria. Based on the results of the study that has been carried out, there are 17 types of antibiotics with a total value of 46,876 DDD / 100 patient days. The three largest antibiotics were ceftriaxone 21,126 DDD/100 patient days, metronidazole 6,790 DDD/100 patient days, and levofloxacin 3,426 DDD/100 patient days. The most common route of administration was intravenous.